右側上顎第三大臼歯部に3 歯の埋伏過剰歯を認めた1例 - 佐々木, 和起; 小野, 重弘; 重石, 英生; 武知, 正晃; 多田, 美里; 太田, 耕司 (日本口腔外科学会雑誌, 2017)
The prevalence of supernumerary teeth is about 1%, and cases of multiple supernumerary teeth are extremely rare. In addition, supernumerary teeth are often found in the anterior maxillary region, but rarely occur in the molar region. We report a rare case of 3 impacted supernumerary teeth in the maxillary third molar region that occurred in a 16-year-old boy who do not have any genetic disorder. Panoramic X-ray films and computed tomography showed 3 supernumerary teeth impacted in the third molar region of right maxilla. All were extracted during a single surgical procedure with the patient under general anesthesia. Each of the supernumerary teeth was found to be incompletely developed, while they were similar to normal permanent molars in both shape and size. The postoperative course was satisfactory, and we are continuing periodic follow-up examinations of the patient.